(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Introduction: Palliative stenting for relieving malignant obstruction of the gastrointestinal tract is routinely practiced in western world. Obstructing advanced GI malignancy requires bypass or exteriorization of proximal gut before NACT or as a bridge to definite surgery. The aim of the study was to review the experience at tertiary cancer hospital and short-term outcome with endoscopic stenting in lieu of palliative bypass surgery for advanced and obstructing GI malignancy. Materials and Methods: This observation study was carried out in the surgical out-patient department of NICRH where all therapeutic endoscopic facilities were available. All patients treated with stenting in a 2 years period from 2018-2020 were studied. Results: Fifty-six patients received 60 stents. No case of perforation occurred. In fifteen cases (26.78%) clogging with food occurred; in 5 cases (8.92%) displacement occur. Tumour overgrowth was noted in 7 (12.66%) cases. Four patients (6.72%) received a second stent. Mean survival of patients with esophageal stent was 221 days. Four patients received 4 stents in their colon or rectum. The stents were placed in the sigmoid (n=2), the descending colon (n=1), and the transverse colon (n=1). Mean survival of colonic stent patients was 331 days. No perforation, no clogging by stool and no tumour ingrowth among patients with colonic stent but one (25%) had displacement. Eighteen patients received a total of 18 stents because of obstructing stomach cancer. 12 (61.22%) patients had tumour at cardia. Mean survival after gastric stent placement was 176 days. There was no perforation, one case of clogging (8.33%), and two cases of tumour ingrowth (16.66%). 5 patients underwent duodenal stenting. Remaining one at Billroth II anastomotic site. Single patients (20%) required laparotomy and stent extraction due to duodenal stent migration. Mean survival after duodenal stent placement was 242 days. No perforation, no clogging and no tumour ingrowth. Conclusions: The present series shows that placement of expandable metallic stents in the obstructing GI tract malignancy as an alternative to bypass surgery is safe, cost effective, low complications, short hospital stay and provides good palliation. J Bangladesh Coll Phys Surg 2024; 42: 241-246